An appraisal of the situation of the palliative care in Poland in 2016 - Ciałkowska-Rysz, Aleksandra; Dzierżanowski, Tomasz (Medycyna Paliatywna/Palliative Medicine, 2018)
The situation and accessibility to palliative care in 2016 was assessed in this paper. The data used in this study come from the websites of the national central and regional divisions of the National Health Fund, the Ministry of Health, the Education Centre for Nurses and Midwives, the Medical Examination Centre, and from the map of healthcare needs in 2014 and the Central Statistical Office. The results revealed that access to guaranteed palliative and hospice services in Poland is diverse, and there are disparities between the voivodeships in the entities count, expenditures per capita, and accessibility to services. The best accessibility refers to the home care, and the worst – to the out-patient clinics. It is necessary to increase not only financial expenditures on the services but also investments in the infrastructure. The quantity of staff in palliative care is quite good, although the increasing demand for palliative care generates growth of the need for specialist staff.